Comparisons of RZ-OOK and RZ-DPSK in dense OTDM-WDM systems using Q factor models - Abbou, F. M.; Chuah, Hean Teik; Hiew, C. C.; Abid, A. (Springer, 2008)
In view of the differential phase Q (DP-Q) and the traditional Q factor, we compared, using numerical simulations, the performances of the RZ-OOK and RZ-DPSK in dense OTDM-WDM systems. When signal pulse widths and optical filter bandwidths are optimized, there is no upper limit to the WDM channel bit rate (BR) in the purely linear back-to-back configuration. Here, RZ-DPSK performed increasingly better than RZ-OOK in a higher spectral density with Q gain increasing from 3 to 5 dB. In the nonlinear point-to-point configuration, a higher BR leads to increased performance penalties for both the RZ-DPSK and RZ-OOK, while the RZ-DPSK still outperforms RZ-OOK by up to 4 dB. The results obtained correlate with conventional results, indicating the potential of the DP-Q as a performance evaluation tool in numerical simulations.